The study of figurative language in Taylor Swift's lyrics in the 'Folklore' album: a pragmatic analysis / Nur Syazmin Ezryn Mohd Yunos and F Peter Francis G Frncis - Mohd Yunos, Nur Syazmin Ezryn; G Frncis, F Peter Francis (Universiti Teknologi MARA, 2023)
Being considered as one prominent literary works, songs laden with figurative language are composed to imply deeper meaning of what is being said. Therefore, this research aims to classify the types of figurative language used in Taylor Swift's lyrics in 'Folklore' album, to analyse the implicature of Figurative Language in Taylor Swift's lyrics in 'Folk-lore' album, and to analytically describe the associative meaning of Taylor Swift's lyrics in 'Folklore' album. This study utilised Kennedy's Theory of Figurative language, Grice's Theory of Implicature as well as Leech's Theory of Associative Meanings. These theories uncovered how non-literal language in Taylor Swift's songs influences lyrical interpretation. This present study adopted a qualitative research method whereby the researcher conducted content analysis on the selected lyrics excerpts from the selected album to achieve the research objectives. Consequently, based on the findings, it was found that metaphor is the most dominant type of figurative language with a frequency of 31.40% while connotative meaning is the most common associative meaning with a frequency of 14.79%. Furthermore, the intended meaning of a figurative phrase can be interpreted with a slight context on what is implied through implicature pragmatics. Therefore, this study revealed that using figurative language in songs connects writers and listeners on a deeper level as it creates new connections between images, ideas or concepts that are not typically associated together with.